Fulfillment of Environmental Rights: Policy Strategies and Their Impact on Sustainable Development - Budiono, Indro (Jurnal Cakrawala Hukum, 2024)
This research explores the role of the Indonesian government in prioritizing the fulfillment of environmental rights through policy strategies and their impact on the countryâ€™s sustainable future. The study examines key government policies aimed at protecting these rights, such as regulations on deforestation, pollution control, and renewable energy initiatives, as well as their effectiveness in addressing challenges like climate change, deforestation, and pollution. Through a combination of policy analysis and case studies, this research investigates how government actions, in collaboration with stakeholders such as businesses, non-governmental organizations (NGOs), and local communities, have influenced environmental sustainability. It also assesses the socio-economic impacts of these policies, including their contributions to environmental conservation, economic growth, and social equity. The findings suggest that while progress has been made, significant gaps remain in enforcement, accountability, and public awareness. Ultimately, the study concludes that a more coordinated, multi-sectoral approach is required to ensure the full realization of environmental rights in Indonesia. It recommends strengthening policy implementation, enhancing collaboration between stakeholders, and promoting greater public participation in environmental governance to achieve a truly sustainable future for the nation. How to cite item: Budiono, Indro. â€œFulfillment of Enviromental Rights: Policy Strategies and Their Impcat on Sustainable Developmnet.â€ Jurnal Cakrawala Hukum 15 no. 1 (2024): 21-36. DOI: 10.26905/idjch.v15i1.14366.